Twinning rates in Ghana - Mosuro, A.A.; Agyapong, A.N.; Opoku-Fofie, M.; Deen, S. (Twin Research, 2001)
The incidence of twin births in Accra and Kumasi, the two major cities in Ghana, was investigated. In Accra, data were collected from the Korle-Bu Teaching Hospital while data were collected and analyzed from the Komfo Anokye Teaching Hospital in Kumasi. Both hospitals are the leading teaching hospitals in Ghana. The data consisted mainly of single and twin births recorded in the hospitals over a period of 12 years in Accra (1988-1999) and 15 years in Kumasi (1985-1999). The study revealed an incidence of 33.4 twin births per thousand live births for Accra and 26.6 twin births per thousand live births for Kumasi. Though these values are not as high as those reported among the Yoruba tribe of southwest Nigeria, who are reported to have the highest twin birth rates in the world, the present values still rank among the highest recorded twin birth rates. © 2001 Cambridge University Press.